PERANCANGAN APLIKASI WEBSITE UNTUK LAYANAN ASPIRASI MAHASISWA DAN MANAJEMEN ORGANISASI DPM FTI UNTAR - Salsabila Azhary Firdaus; Tony (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
The Student Representative Council of the Faculty of Information Technology, Tarumanagara University (DPM FTI Untar) is a student legislative body that plays an important role in facilitating student aspirations with the faculty. The main problem faced is the lack of integrated aspiration management system and digital organization management. This research aims to develop a web application that facilitates the management of student aspirations, member attendance system, and organizational archive management to increase transparency and student participation. The application development uses the Agile Software Development Life Cycle (SDLC) methodology which includes the stages of requirements analysis, interface design, system development, testing, and documentation. The design wants to be built using the PHP programming language and MySQL database. This research also includes an analysis of the DPM FTI organizational structure, database design, and infrastructure specifications needed to support application implementation. The results of this research are expected to optimize the process of managing student aspirations and organizational management of DPM FTI Untar in a more efficient, structured, and integrated manner.